OUTPUT COSTS STANDARD ANALYSIS OF AUDIT AT THE SUPREME AUDIT BOARD OF INDONESIA (BPK RI) - Wijati, Iman Sapto; kholis, Nur (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study aims at seeking the composing process of output cost standard for auditactivities at the Supreme Audit Board Republic of Indonesia (BPK RI ), finding out theaudit cost components based on the output cost standard, and analyzing the fairness ofaudit expenditure. This study used qualitative method research while the expenditureanalysis method used linear regression model. As public sector organization, BPK has anobligation to compose the budget planning (RKA K/L). One of those instruments is theoutput cost standard (SBK). According to the result of study, the audit process is startedby formatting the composer of SBK team, determining the type of output activity and thefare of output cost standard, reviewing and analyzing the data, doing communicationprocess, proposing process, and also composing process of SBK implementation. Theaudit cost components are meeting cost, stationery cost, speaker honorarium, travel cost,investigation cost, laundry cost, physical check cost, survey cost, delivery worksheetpaper cost, laboratory cost, and printing report cost. The result of this study which isused a simple linear regression model showed that there are five units which have totalspending exceeds the average of expenditure.Keywords: The Supreme Audit Board Republic of Indonesia, output standard costs, audit,simple linear regression.